ASSESSMENT OF MICROBIOLOGICAL QUALITY OF COMMERCIALLY PREPARED READY TO DRINK TIGERNUTS SOLD IN OWERRI, IMO STATE. - Nwachukwu, Innocentia Ogechi (Int'l Journal of Education Research and Scientific Development, 2024)
Assessment of microbiological quality of commercially prepared ready to drink tiger-nuts sold in Owerri, Imo State was carried out using serial dilution and pour plate technique. Tiger-nut were washed, blended and sieved to liquid extract. Aliquots of serially diluted tigernuts were inoculated unto a freshly prepared nutrient agar, MacConkey agar for bacteria isolates and incubate for 370C for 24hrs while Sabouraud dextrose agar for fungi isolates was incubated for 250C for 72hrs. Identification of pure culture was done using morphological characteristics and biochemical test. The total bacteria and fungi count showed the occurrence of bacteria isolated indicating that Bacillus sp (42.8%) was higher followed by Klebsiella sp (28.6%) and Staphylococcus aureus (28.6%). While fungi occurrence showed that Rhizopus sp (40%) was higher followed by Sacharomyces sp (33.3%), Aspergillus sp (13.4%) and Penicillium sp (13.3%). Therefore, the microbial status of the samples showed that bacteria and fungi species affect the quality of tiger nut. It will be necessary, however, to determine the effects of storage in different packaging materials at refrigeration and ambient temperatures on the microbiological status of tigernut milk extract to ascertain its shelf-life